Compósitos de matriz polimérica com Resíduos da Construção e Demolição (RCD) e fibras de sisal - ALENCAR, Krishana Carvalho de (2022)
With the impacts generated by industrial waste on the environment and the need for natural and renewable sources, research has been carried out to produce new materials using waste and plant fibers, such as composite materials. In this work, polymeric composite materials were produced with Construction and Demolition Waste (RCD), with a granulometry of 100 mesh, and the addition of sisal fibers, in a length of 15 mm. Hybrid composites were made by the manual method (hand lay-up) associated with compression, with mass fractions of waste ranging from 5% to 25% and with fractions of 3% of sisal fibers. The matrix used was isophthalic polyester resin together with catalytic materials. Mineralogical characterization was performed on the residue and morphological characterization on the residue and fiber. Physical, mechanical tensile and horizontal flammability tests were carried out on the composites produced. The mineralogical analysis of the residue showed the main peaks of Quartz and Calcite. The morphological analysis of the residue identified different shapes of particles, and that of the fiber indicated the presence of a rough surface. It was observed that the physical properties increased as the proportions increased. The tensile strength analysis indicated superior results to the full matrix for the composites produced, and the composition with 20% RCD and 3% Sisal Fibers had the best tensile performance (16,92 MPa). Regarding flammability, there was a reduction in the burning rate as residue and fibers were inserted into the polymeric matrix, where the composition with 25% of RCD and 3% of Sisal Fibers obtained the best result in relation to the full matrix (51,44%) and with a reduction of 87,04% and 82,72% for CONTRAN 498 and ASTM D 635, respectively. Based on the study, the reuse of construction and demolition waste and the use of sisal fibers is a viable alternative for the production of new materials that replace the conventional ones, for application in ceilings, panels, partition walls, as they have good properties and are sustainable.